Systematic Literature Review: The Role of Trauma and Resilience in Modulating Prosocial Behavior - Annisa Arifatuwilma; Neviyarni S (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
Traumatic experiences can shape individual socio-emotional development and influence the emergence of prosocial behavior. This article aims to investigate how trauma relates to prosocial behavior and examine the role of resilience in modulating this relationship. Using a systematic literature review, empirical articles published between 2014 and 2024 were identified from international scientific databases with inclusion criteria focusing on trauma, resilience, and prosocial outcomes. Twenty-seven eligible studies were synthesized using narrative analysis based on thematic categorization. Overall results show that trauma tends to have a negative effect on prosocial behavior, particularly among individuals exposed to violence or disaster, while resilience consistently appears as a mechanism that weakens or transforms this effect into adaptive social responses. Several reviewed studies also indicate the possibility of prosocial development following adversity when resilience and social support are present. This review contributes conceptually by emphasizing resilience as a key psychological process underlying variations in posttraumatic prosocial outcomes and provides implications for intervention and prevention strategies aimed at strengthening adaptive resources in individuals who experience adversity.Keywords: prosocial behavior, traumatic, resilience